2004
DOI: 10.1167/iovs.03-1047
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Gene Expression after Injury in the Rat Retina

Abstract: The use of microarray technology enables definition of complex genetic changes underlying distinct phases of the cellular response to retinal injury. The early response clusters genes associate with the transcriptional regulation of the wound-healing process and cell death. Most of the genes in the late, sustained response appear to be associated with reactive gliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 38 publications
10
105
0
Order By: Relevance
“…Recent studies have shown that levels of alpha-crystallins are considerably elevated in models of light toxicity and retinal tearing and suggested they play a crucial role in the protection of retinal tissue [27,28]. Alpha-crystallin may also play a significant role in the pathophysiology of neurodegenerative disorders.…”
Section: Expression Of Heat Shock Proteins In the Eyementioning
confidence: 99%
“…Recent studies have shown that levels of alpha-crystallins are considerably elevated in models of light toxicity and retinal tearing and suggested they play a crucial role in the protection of retinal tissue [27,28]. Alpha-crystallin may also play a significant role in the pathophysiology of neurodegenerative disorders.…”
Section: Expression Of Heat Shock Proteins In the Eyementioning
confidence: 99%
“…Similarly, of the 27 reported genes between E18 and P14 in corticospinal motor neurons that were found in the RGC GeneChip dataset, only two were developmentally regulated in RGCs (Purkinje cell protein 4 and neurofilament-H). We also compared P21 RGC gene expression with adult retinal gene expression published previously (Vazquez-Chona et al, 2004) using triplicate biological samples and data from the Affymetrix U34A GeneChips (ϳ8800 probes). Of the 3566 genes present in at least two of three P21 RGC samples, most were also observed in retina (Fig.…”
Section: Retinal Ganglion Cell Gene Expressionmentioning
confidence: 99%
“…They are evolutionarily related to certain microorganism stress proteins and to vertebrate proteins associated with processes of cellular differentiation and morphological change (Wistow, 1995). Various β,γ-crystallins are present in low abundance in tissues other than the lens, most prominently in the retina (Andley, 2007) where their expression is reported to be upregulated following various injuries or stresses (Sakaguchi et al, 2003;Vazquez-Chona et al, 2004;Crabb et al, 2002). βB2-crystallin has recently been reported to be secreted by the retina in culture where it promotes the regrowth of retinal ganglion cell axons (Liedtke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%